Higher melatonin in the follicle fluid and MT2 expression in the granulosa cells contribute to the OHSS occurrence - Yiran Li; Lanlan Fang; Yiping Yu; Hao Shi; Sijia Wang; Yanjie Guo; Yingpu Sun (BMC, 2019)
Abstract Background Ovarian hyperstimulation syndrome (OHSS) is a common and severe complication for patients undergoing IVF/ICSI-ET. Melatonin widely participates in the regulation of female reproductive endocrine activity. However, whether melatonin participates in the progression of OHSS is largely unknown. This study aims to identify the predictive value of follicular fluid (FF) melatonin for OHSS establishment and the underlying mechanism. Methods All participants of this case-control study were enrolled at the Reproductive Medicine Center located in the First Affiliated Hospital of Zhengzhou University in China from January to October in 2017. Quantitative real-time PCR and western blot were used to examine the mRNA and protein levels. Primary granulosa cells were extracted and cultured for in vitro studies. Melatonin concentration was measured by ELISA. Logistic analysis and receiver-operating characteristic (ROC) curves were used to evaluate the predicting value of melatonin on OHSS occurrence. Main outcome measures The expression level of melatonin receptor 2 (MT2), P450 aromatase cytochrome (aromatase), vascular endothelial growth factor (VEGF), and inducible nitric oxide synthase (iNOS) mRNA in human primary granulosa cells. The concentration of melatonin in FF. The predicting value of melatonin on OHSS and the cut-off value of the prediction. Results FF melatonin concentrations were significantly higher in patients with OHSS compared to non-OHSS group (35.94 ± 10.18 ng/mL vs 23.93 ± 10.94 ng/mL, p<0.001). The expression of MT2 mRNA (p = 0.0459) and protein in granulosa cells was also significantly higher in the OHSS group. When using a cut-off level of 27.52 ng/ml, the sensitivity and specificity of FF melatonin to predict OHSS was 84.6 and 74.0%, respectively (p < 0.0001). We also found that melatonin could up-regulates aromatase mRNA, VEGF mRNA expression and down-regulates iNOS mRNA expression in the granulosa cells. Conclusion OHSS patients have higher melatonin in the FF as well as higher MT2 expression in the granulosa cells. The melatonin in FF might be used as an effective predictor for the occurrence of OHSS.